The Relationship between Individual Characteristics, Physical Workload and Mental Workload with Work Fatigue in Production Section Employees at PT. X - Sindi Larasati; Suroto Suroto; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Work fatigue can inhibit the work activities of employees of the production section because it results in decreased work power and reduced endurance to work. Preliminary survey results show that 70% of employees experience stiff complaints, 90% had heavy physical activity, 90% require high accuracy and 90% lack of rest. The purpose of this research was to analyze the correlation between individual characteristics, physical workload and mental workload on the employees of the production section at PT. X. This type of research uses quantitative methods, with cross-sectional studies. The population in this study amounted to 120 employees who work on the morning shift using the proportionate stratified random sampling technique obtained a sample of 45 employees. Work fatigue was measured using the Industrial Fatigue Research Committee (IFRC) questionnaire, physical workload was measured using a pulse oxymeter, mental workload was measured using a NASA-TLX questionnaire, nutritional status was measured using microtoise and weight scales. Statistical analysis used was the chi-square test and the Spearman rank test. The results showed that there was a significant relationship between physical workload (p-value 0.006), exercise frequency (p-value 0.021) and nutritional status (p-value 0.014) with work fatigue, there was no relationship between age (p-value 0.196), years of service (p-value 0.107), smoking habits (p-value 0.576) and mental workload (p-value 0.331) with work fatigue. Based on these results the researcher gives a suggestion that is stretching on the sidelines of work and doing exercise at least 3 times a week.